Importance of Development of Ecological Tourism in Uzbekistan - Abduraimova Nilufar Ulugbek kizi, (European Journal of Life Safety and Stability (2660-9630), 2024)
This article presents thoughts and opinions about the importance and benefits of developing ecological tourism in Uzbekistan.